1988
DOI: 10.1002/j.1537-2197.1988.tb13483.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Leaf Variegation in Saintpaulia Ionantha During in Vitro Propagation and During Chimeral Separation of a Pinwheel Flowering Form

Abstract: Plants of the foliarly variegated cultivar Saintpaulia ionantha Tommie Lou and the florally variegated cultivar Candy Lou were regenerated through tissue culture from leaf sections, petal sections, and subepidermal tissue. This provided explants with derivatives of all histogen layers of the shoot apex, layers I and II only, and layers II and III only. Over 1,000 plants of Tommie Lou and Candy Lou were grown to flowering. A low level of phenotypic variation was observed, but in no case could this be attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Segregation of chimeras into pure plants containing only one type of component cells is a long-established topic (Canli, 2003;Canli and Skirvin, 2008;Chua et al, 1981;Hall et al, 1986;Marcotrigiano et al, 1987;Skirvin, 1983, 1989;Ning et al, 2009;Peary et al, 1988;Rosu et al, 1995;Roy et al, 2001). The mechanism was primarily explained using the theory of the tunica-corpus pattern of the meristematic region described by Schmidt (1924) and later refined by Tilney-Bassett (1986, 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Segregation of chimeras into pure plants containing only one type of component cells is a long-established topic (Canli, 2003;Canli and Skirvin, 2008;Chua et al, 1981;Hall et al, 1986;Marcotrigiano et al, 1987;Skirvin, 1983, 1989;Ning et al, 2009;Peary et al, 1988;Rosu et al, 1995;Roy et al, 2001). The mechanism was primarily explained using the theory of the tunica-corpus pattern of the meristematic region described by Schmidt (1924) and later refined by Tilney-Bassett (1986, 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Periclinal chimeras remain stable when propagation does not provoke the reorganization of cell layers (Marcotrigiano, 1997;Frank and Chitwood, 2016). Adventitious meristem formations generally arise from a single cell in many plants (Boertjes et al, 1968;Yang et al, 2017), often with only the participation of the L1 epidermal layer (Boertjes and Van Harten, 1985;Peary et al, 1988;Yang et al, 2017). Nevertheless, histological analyses revealed that all of the cell layers can be at the origin of an adventitious meristem, with the possibility of a multicellular origin, sometimes leading, even in small proportions, to variegated plants arising from adventitious regeneration (Marcotrigiano, 1986;Nabeshima et al, 2017).…”
Section: Variegation Stability Is Influenced By the Origin Of New Sho...mentioning
confidence: 99%
“…In vitro segregation of the component genotypes of chimeral plants has been observed in several herbaceous micropropagation systems [4,6,7,8,16,18,21,22,28], with fewer reports on woody plants [5,24,30]. While Rhododendron micropropagation is well documented [1,2,3,9,10,11,12,13,14,15,17,23,25,26], whether multiplication proceeds by axillary or adventitious shoot growth has not been documented.…”
Section: Introductionmentioning
confidence: 99%